Les Madrilènes et les espaces de la ville : de Surcos (José Antonio Nieves Conde, 1951) à Barrio (Fernando León de Aranoa, 1998) - Marianne Bloch-Robin (Cahiers de Civilisation Espagnole Contemporaine)
In the construction of the city filmic spaces, the inhabitants constitute a key element, as well as filmic processes, visual or sound. Through six emblematic films produced throughout the second half of 20th century, we analyze how the representation of Madrid inhabitants evolves, what its functions and characteristics are in the construction of urban and suburban spaces and how it changes depending of the time frame and the singular views of the film directors.